Fatigue Damage Simulation Of Automobile Steering Knuckle Subjected To Variable Amplitude Loading - Ad Suhadak, Fadrah Hanim; Zakaria, Kamarul Ariffin; Ali, Mohd Basri; Yusuff, Mohd Asri (KKG Publications, 2017)
Fatigue damage assessment is essential in determining the durability of automobile components. Several studies have been conducted on fatigue durability of steering knuckle using constant amplitude loading. However, most of the engineering structural and components are subjected to Variable Amplitude Loadings (VALs) in service. Therefore, this study aims to present a fatigue damage simulation of automobile steering knuckle of a 1300 cc national automobile using finite element analysis. In this study, the steering knuckle is modeled using computer-aided design software, in which the dimensions are assigned according to 3D scanning files. The critical area on the steering knuckle is determined using commercial finite element software. The strain gauge is then mounted on the steering knuckle and connected to a data acquisition system to capture the actual fatigue strain signal while driving on a residential road. The fatigue strain signal is then used as the VAL in the fatigue damage simulation of automobile steering knuckle. Forged steel, cast aluminum, and cast iron are used and analyzed in the simulation. Results indicate that the different types of material used significantly influenced the fatigue damage of the automobile steering knuckle.